The Influence of Job Satisfaction and Career Development on Employee Performance at the Balai Office Animal, Fish and Plant Quarantine Central Sulawesi - Stephani Pratiwi Tumonggi; Andi Indriani Ibrahim; Harnida Wahyuni Adda; Mohammad Ega Nugraha (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of job satisfaction and career development on employee performance at the Animal, Fish, and Plant Quarantine Office of Central Sulawesi. The population in this study were all employees at the Animal, Fish, and Plant Quarantine Office of Central Sulawesi, totaling 59 people. The sampling technique used saturated sampling where the entire population became respondents in this study. Data were collected through questionnaires and analyzed using multiple linear regression analysis. Before testing the hypothesis, the data were tested through validity tests, reliability tests, and classical assumption tests including normality tests, multicollinearity tests, and heteroscedasticity tests. The results of the study indicate that partially job satisfaction has a significant effect on employee performance, and career development also has a significant effect on employee performance. Simultaneously, job satisfaction and career development have a significant effect on employee performance. The coefficient of determination shows that 58.8% of the variation in employee performance can be explained by job satisfaction and career development, while the rest is influenced by other factors outside the research model. The implications of this study indicate that increasing job satisfaction and implementing effective career development programs are important strategies in improving employee performance in government agencies, especially at the Animal, Fish, and Plant Quarantine Office of Central Sulawesi